Perfluorohexyloctane ophthalmic solution for dry eye disease: pooled analysis of two phase 3 clinical trials - Fahmy, Ahmad M.; Harthan, Jennifer S.; Evans, David G.; Greiner, Jack V.; Tauber, Joseph; Sheppard, John D.; Krösser, Sonja; Vittitow, Jason L. (Frontiers in Ophthalmology, 2024)
BackgroundDry eye disease (DED) is commonly caused by excessive tear film evaporation due to Meibomian gland dysfunction (MGD). There is a need for DED treatment options that address tear evaporation and benefit patients across a broad range of demographic and disease characteristics. This study evaluated treatment effects of perfluorohexyloctane ophthalmic drop (formerly NOV03) in the pooled dataset from 2 pivotal clinical trials in patients with DED associated with MGD, both in the overall population and in patient subgroups based on sex, age, and baseline severity of eye dryness.MethodsPooled data from 2 similarly designed, phase 3, randomized controlled trials (GOBI, MOJAVE) were analyzed. Patients aged ≥18 years with DED administered perfluorohexyloctane (n=614) or hypotonic (0.6% solution) saline control (n=603) four times daily for 8 weeks. Primary endpoints were total corneal fluorescein staining (tCFS) score (National Eye Institute scale, 0-15) and eye dryness visual analog scale (VAS) score (0-100). Efficacy was evaluated using analysis of covariance among patient subgroups (male and female, older [≥65 years] and younger [18 to <65 years], tCFS score <7 and ≥7, VAS eye dryness score <70 and ≥70, MGD score <7 and ≥7, Schirmer I test <10 mm and ≥10 mm).ResultsReductions in tCFS and VAS eye dryness scores were greater for perfluorohexyloctane versus control. In the overall patient population, least-squares mean treatment difference was −1.1 (95% CI: −1.41 to −0.79; p<0.0001) for tCFS and −9.0 (95% CI: −11.90 to −6.00; p<0.0001) for VAS eye dryness. Treatment favored perfluorohexyloctane over control in all patient subgroup analyses of tCFS and VAS eye dryness. Overall, the most common adverse event with perfluorohexyloctane was blurred vision (2.1% of patients), which was mild and transient.ConclusionsCompared with a hypotonic saline control, perfluorohexyloctane improved both the signs and symptoms of DED, including in patients with greater self-reported severity of eye dryness.Clinical trial registrationThis study represents an integrated analysis of 2 previous clinical trials: GOBI (ClinicalTrials.gov, NCT04139798) and MOJAVE (ClinicalTrials.gov, NCT04567329).